Perceived service quality and culture of health safety in the medical staff of the Hospital II EsSalud Vitarte. Lima, 2017 - Podestá Gavilano, Luis Enrique (2018)
Objective: To determine the relationship between perceived service quality and culture of health safety in the medical staff of a level II hospital in the district of Vitarte, city of Lima. Materials and methods: A quantitative, descriptive, cross-sectional, correlational, prospective and non-experimental study was carried out in 124 physicians of the Hospital II EsSalud Vitarte in the city of Lima, who were interviewed between March and April 2017. The descriptive analysis was performed by means of a frequency distribution. For the bivariate analysis, the Kendall's tau (τ) coefficient was used, and p < 0.01 was considered for significant differences. Results: A positive relationship was found between perceived service quality and culture of health safety among the physicians. Conclusions: The perceived service quality is significantly related to the culture of health safety in the medical staff of the Hospital II EsSalud Vitarte, Lima, 2017.